2021
DOI: 10.1186/s13002-021-00444-1
|View full text |Cite
|
Sign up to set email alerts
|

Entomotherapy: a study of medicinal insects of seven ethnic groups in Nagaland, North-East India

Abstract: Background The ethnic communities in Nagaland have kept a close relationship with nature since time immemorial and have traditionally used different kinds of insects and their products as folk medicine to treat a variety of human ills and diseases. The present study was conducted to record the entomotherapeutic practices of seven different ethnic groups of Nagaland. Method Documentation is based on semi-structured questionnaires and group discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 42 publications
1
34
0
1
Order By: Relevance
“…Our study revealed nineteen (19) medicinal insects used by traditional healers, showing very rich ethnomedicine knowledge in the two provinces of Burkina Faso. There are similarities with other studies carried out in the world generally, and in Africa specifically, where bees (Hymenoptera) and their products, but also beetles (Coleoptera) and cockroaches (Blattodea), were predominant in the list of the therapeutic species [ 11 , 14 , 18 ] . Thus, insect and insect-derived products provide ingredients that have been a staple in traditional medicine for centuries in many parts of the world.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our study revealed nineteen (19) medicinal insects used by traditional healers, showing very rich ethnomedicine knowledge in the two provinces of Burkina Faso. There are similarities with other studies carried out in the world generally, and in Africa specifically, where bees (Hymenoptera) and their products, but also beetles (Coleoptera) and cockroaches (Blattodea), were predominant in the list of the therapeutic species [ 11 , 14 , 18 ] . Thus, insect and insect-derived products provide ingredients that have been a staple in traditional medicine for centuries in many parts of the world.…”
Section: Discussionsupporting
confidence: 76%
“…can be used to treat different health problems [ 14 , 15 ]. Insect therapy can be an excellent avenue for drug research regarding the great diversity in this group [ 11 – 13 , 16 18 ]. This requires a deep knowledge of the medicinal insects, their chemical composition and their potential applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected respondents were asked about the local usage and names of invertebrates and herpetofauna. The corresponding photographs for each species (N = 30) were then identified using field guides and secondary sources ( Greig-Smith, 1983 ; Phillips, 1994 ; Kakati et al, 2006 ; Oksanen et al, 2013 ; Team, 2013 ; Altaf et al, 2018 ; Mozhui et al, 2021 ; Mussarat et al, 2021 ; Haq et al, 2022 ) with the help of a local taxonomist from the zoology department at Baba Ghulam Shah Badshah University in Rajouri, J&K, India. Taxonomic verification was also carried out by using the online databases “Integrated Taxonomic Information System” ( https://www.itis.gov ) and IUCN’s Red List of Threatened Species ( https://www.iucnredlist.org ).…”
Section: Methodsmentioning
confidence: 99%
“…Some natural toxins are produced by insects in their special organs, such as bee venom and cantharidin [ 109 , 110 ]. The giant water bug L. indicus , which is consumed as both a medicinal and edible insect [ 111 ], could produce complex chemicals in its odorous gland [ 112 , 113 ]. On the other hand, some other components from insects are enriched and accumulated from the plants, fungi, and algae that they feed on.…”
Section: Nutritional and Health Benefits Of Edible Aquatic Insectsmentioning
confidence: 99%